Patient-reported outcome measures after hip fracture in patients with chronic cognitive impairment: results from 34, 675 patients in the Norwegian Hip Fracture Register. (5th July 2021) - Kristoffersen, Malfrid H.; Dybvik, Eva H.; Steihaug, Ole M.; Kristensen, Torbjørn B.; Engesæter, Lars B.; Ranhoff, Anette H.; Gjertsen, Jan-Erik
Abstract : Aims: Hip fracture patients have high morbidity and mortality. Patient-reported outcome measures (PROMs) assess the quality of care of patients with hip fracture, including those with chronic cognitive impairment (CCI). Our aim was to compare PROMs from hip fracture patients with and without CCI, using the Norwegian Hip Fracture Register (NHFR). Methods: PROM questionnaires at four months (n = 34, 675) and 12 months (n = 24, 510) after a hip fracture reported from 2005 to 2018 were analyzed. Pre-injury score was reported in the four-month questionnaire. The questionnaires included the EuroQol five-dimension three-level (EQ-5D-3L) questionnaire, and information about who completed the questionnaire. Results: Of the 34, 675 included patients, 5, 643 (16%) had CCI. Patients with CCI were older (85 years vs 81 years) (p < 0.001), and had a higher American Society of Anesthesiologists (ASA) classification compared to patients without CCI. CCI was unrelated to fracture type and treatment method. EQ-5D index scores were lower in patients with CCI after four months (0.37 vs 0.60; p < 0.001) and 12 months (0.39 vs 0.64; p < 0.001). Patients with CCI had lower scores for all dimensions of the EQ-5D-3L pre-fracture and at four and 12 months. Conclusion: Patients with CCI reported lower health-related quality of life pre-fracture, at four and 12 months after the hip fracture. PROM data from hip fracture patients with CCI are valuable in the assessment of treatment. Patients with CCI should be included in future studies. Cite this article: Bone Jt Open 2021;2(7):454–465.